Sympathetic blocks for the treatment of complex regional pain syndrome: A case series. Issue 19 (May 2018) - Gungor, Semih; Aiyer, Rohit; Baykoca, Buse
Abstract: Rationale: To present the successful treatment of complex regional pain syndrome type -1 utilizing sympathetic blocks. Patient concerns: Severe pain interfering with activities of daily living and temporary disability secondary to complex regional pain syndrome. Diagnoses: Complex regional pain syndrome type-1 with involvement of lower extremity (2 patients), and upper extremity (1 patient). Interventions: We report the management of 3 patients with diagnosis of complex regional pain syndrome type-1 by early institution of sympathetic blocks for diagnostic and therapeutic purposes. All 3 patients were able to tolerate physical therapy only after adequate pain relief had been achieved with institution of sympathetic blocks. Outcomes: All 3 patients responded very favorably to sympathetic blocks with dramatic reversal of pathology. All patients reported almost complete resolution of pain, symptoms, and signs within 6 months duration after diagnosis of complex regional pain syndrome. All 3 patients were able to wean their pain medications and achieve normal activities of daily living without any significant limitations. All patients were able to return to full-time employment. Lessons: Treatment options are limited and there is lack of high quality research regarding the efficacy of sympathetic blocks in the treatment of complex regional pain syndrome. As presented in this case series, sympathetic blocks maybe very effective in the treatment of complex regional pain syndrome in a subset of patients. Thus, early institution of sympathetic blocks should be considered in complex regional pain syndrome prior to physical therapy and consideration of more invasive pain management interventions.